2019
DOI: 10.31764/ijeca.v2i3.2143
|View full text |Cite
|
Sign up to set email alerts
|

Countering Zeitgeist of Self-Centered through Role Playing Methods among Junior High School Students

Abstract: This study aimed to examine the influence of role playing methods on the cognitive, affective, and psychomotor aspects of students in Christian education subjects, as an effort to counter zeitgeist of self-centered. Role playing method can give a strong and durable sense of learning in the students' memories, be a fun learning experience that is difficult to forget, make the classroom atmosphere more dynamic and enthusiastic, arouse passion and spirit in students and foster togetherness, allow students to plun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The more remarkable improvement in experimental group students taught by the role-playing method shows that this method has better potential for student learning outcomes. Other researcher confirmed the same findings on improvement of learning outcome [10][11][12]. These findings discussed the role-playing in many levels and field of studies.…”
Section: Discussionsupporting
confidence: 74%
“…The more remarkable improvement in experimental group students taught by the role-playing method shows that this method has better potential for student learning outcomes. Other researcher confirmed the same findings on improvement of learning outcome [10][11][12]. These findings discussed the role-playing in many levels and field of studies.…”
Section: Discussionsupporting
confidence: 74%
“…It was impossible to get proper education process in pandemic era. Even a year before pandemic, a research proved that teachers needed an extra hard effort to design the learning process so that students are interested in participating in teaching and learning activities [1]. It was found that role playing method influenced 34,8% on the result.…”
Section: Introductionmentioning
confidence: 99%
“…According to Djamarah, and Zain, the method of discussion was "how the lesson was presented, in which students were faced with an issue which can be a problematic statement or question to be discussed and solved together." [2] Inside this method of discussion virtually was expected to have interactions between two or more individuals involved, exchanging each other's experiences, giving information, solving problems and expected everything was active, there was nothing passive as a listener only, especially in Christian education [3].…”
Section: Starting Virtual Discussionmentioning
confidence: 99%